1993
DOI: 10.1063/1.354566
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric, dielectric, and elastic properties of poly(vinylidene fluoride/trifluoroethylene)

Abstract: The symmetry-predicted nonzero components of the piezoelectric coefficient, dielectric constant, and elastic compliance matrices have been determined on poly(vinylidene fluoride/trifluoroethylene)(75/25) copolymer at room temperature and a frequency of 500 Hz. The temperature dependence of each of the complex piezoelectric coefficients and complex dielectric constants has been measured in the temperature range of −100 to 65 °C. The frequency dependence of these coefficients has also been measured at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 8 publications
1
42
0
1
Order By: Relevance
“…Also, we assume that dielectric permittivity of FE matrix is isotropic. This is indeed the case for a number of relaxor FE polymers (for example, P(VDF-TrFE), [65]). Even if FE crystal is anisotropic it is unlikely that such an anisotropy persists in granular materials.…”
Section: Applicability Of Resultsmentioning
confidence: 99%
“…Also, we assume that dielectric permittivity of FE matrix is isotropic. This is indeed the case for a number of relaxor FE polymers (for example, P(VDF-TrFE), [65]). Even if FE crystal is anisotropic it is unlikely that such an anisotropy persists in granular materials.…”
Section: Applicability Of Resultsmentioning
confidence: 99%
“…Taking the data of the dielectric constant and elastic modulus, it can be estimated from Equation 5 that a Maxwell-stress-induced strain accounts for ±0.87 % of the thickness strain if a Poisson's ratio of 0.4 is assumed. [19] The two strains combined account for more than 75 % of the total observed strain response for a composite with Figure 6. The strain amplitude S A as a function of the applied-field amplitude E A measured at room temperature for the composites with f = 0.127 (dots) and 0.23(circles) of PANI volume concentration.…”
Section: Full Papermentioning
confidence: 99%
“…The diffraction results suggested that the matrix P(VDF-TrFE) systems have an all-trains (TTTT) conformation [11,12]. Specifically, there were repeated units of a carbon back bone with two hydrogen and two fluorine atoms of the all-trains (TTTT) conformation as β-phase [13]. The all-trains (TTTT) conformation was formed by a net dipole moment pointing from relatively electronegative fluorine to hydrogen [13].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, there were repeated units of a carbon back bone with two hydrogen and two fluorine atoms of the all-trains (TTTT) conformation as β-phase [13]. The all-trains (TTTT) conformation was formed by a net dipole moment pointing from relatively electronegative fluorine to hydrogen [13]. The ensembles of the alltrains (TTTT) conformation collectively contributed to the piezoelectric property of the bulk P(VDF-TrFE).…”
Section: Methodsmentioning
confidence: 99%